STUDI TENTANG PELAKSANAAN PENGAJARAN BAHASA INGGRIS DI SD KOTA TENGGARONG - Didi Sudrajat (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
The objective of this research is to describe English teachers' competency in selectingand developing, designing materials, doing teaching and learning process, using media and learning sources, and evaluating and making test. The design of this study was a survey that used descriptive analysis. This study revealed that the implementation of English teaching at elementary schools in Tenggarong municipality was poor. Similarly, teachers' competency in selecting, developing, anddesigning material, in doing teaching and learning process, in usingmedia and learning sources, and in evaluating and making test was also low or weak.